Active Zone Constructions in Shape Adjectives: An Example of the Adjective Yuvarlak - Ayşe Eda GÜNDOĞDU (Dilbilim Araştırmaları Dergisi)
Cognitive semantics, which has gained acceleration in the last ten years, is a point of view that sees individual’s perception and cognitive level as variables in meaning production process. Utilizing theories in psychology, one of the most important concepts put forward in the aforesaid discipline is active zones, which argues that meaning is a production related to conceptualization and perception. Active zone constructions in adjectives can be discussed as a cognitive structure that helps to display under what conditions and how the cognitive mappings of the adjective and the described noun can vary. In this study, it is aimed to reveal the dynamics in active zone constructions in Turkish shape adjectives in terms of the adjective yuvarlak. Within this perspective, co-occurrence appearances of the research topic adjective are obtained through Turkish National Corpus v3 and active zone constructions are analysed with content analysis method.